Teknologi Subtitusi Bahan Dalam Pengembangan Usaha Mikro Pakan Organik Berprotein - Dumasari, Dumasari (AJIE (Asian Journal of Innovation and Entrepreneurship), 2020)
This article aims to review the urgency of the use technology substitution of materials in the development of micro enterprises organic feed with protein. Existence of micro enterprises organic feed with protein have economic value, social, and environmental for efforts to empower peasants. With the technology of substitution of materials, micro enterprises can contribute to the improvement of peasants income. Ingredients by protein organic feed derived from various types of agricultural waste. This type of enterprises is also potentially reduce the economic burden of peasants because it is easier to feed for fresh water fish with a low cost.